ACCRUAL EARNINGS MANAGEMENT, ASSETS TANGIBILITY, DAN FAKTOR LAINNYA YANG MEMENGARUHI FIRM VALUE - Julisar Surjadi; Chalvin Alfiyandi Damanik (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to analyze and obtain empirical evidence related to the effect of each variable firm size, profitability, leverage, dividend, assets tangibility, liquidity, total asset turnover, and accrual earnings management on firm value. Purposive sampling is a sample selection method in this study. Non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2020 are the sample population in this study. The total population in this study is 645 non-financial companies with a total sample of 327 companies that have met the research criteria for the period 2017 to 2020. This study uses the logit model (logistic regression). The results of this study found that profitability, leverage, dividend, and assets tangibility variables have a positive effect on firm value. Meanwhile, the variable accrual earnings management has a negative effect on firm value. The results of this study also found that firm size, liquidity, and total asset turnover had no effect on firm value.